Fifteen-minute consultation: Recognising and addressing rude, undermining and bullying behaviour. Issue 6 (13th May 2020) - Jacob, Hannah; Baverstock, Anna; Kingdon, Camilla C
Abstract : We set ourselves very high standards at work and when there is a sense that somehow we have failed, we are left feeling disappointed and frustrated. We all set very high standards for ourselves. When those feelings are exacerbated by the embarrassment of a public dressing down, especially if there isn't an opportunity to explain just how difficult the situation had been, we are left feeling angry and let down. Most of us learn how a bully behaves in the playground or at nursery school—and yet, when it happens as an adult at work we often fail to realise what is happening. Harassment or undermining behaviour can be more challenging to identify because it isn't always obvious and can happen without colleagues being aware. Sometimes, it isn't even apparent to those who experience it, until an event means the problem becomes overwhelming. In fact, many people who experience undermining at work perceive the problem as their own and this can have a far more insidious impact on well-being, professional performance and mental health.